Influence of maturation and determinants of repeated-sprint ability in youth basketball players - Gonzalo-Skok, O.; Bishop, C. (The Journal of Strength and Conditioning Research, 2024)
The main aims of the current study were (a) to determine the main predictors of general and specific repeated-sprint ability (RSA) tests, (b) to analyze the relationships between RSA tests and independent measures of physical performance, (c) to examine whether between-age differences exist, and (d) to assess whether maturation affects those mentioned above in young basketball players. Thirty-five young (U-14 to U-16), highly trained basketball players performed a linear sprint test (5, 10, and 25 m), an incremental running test, and 2 repeated-sprint tests (general [RSG]: 6 × 25 m; specific [RSS]: 6 × 5 + 5 m with a 45° change of direction and 20 seconds of passive recovery in both tests). Anthropometric variables were measured and used to calculate age at peak height velocity (APHV), which was used to determine maturation. The main determinants of RSA tests were aerobic performance and linear sprinting for RSS (R2 = 0.84) and adding the percentage of body fat for RSG (R2 = 0.94). Almost perfect relationships (r = 0.93-0.99) were found between all RSA variables (i.e., the best [RSGb and RSSb] and mean time [RSGm and RSSm]). As age increased, performance in RSA was evident, as shown by improved best and mean scores. When APHV was controlled for, no significant differences were apparent in the comparison from U-14 and U-16 in 25 m, RSGb, and RSGm. By contrast, significant differences (p < 0.05) were still evident with APHV controlled between U-14 and U-16 in 5 m, 10 m, RSSb, and RSSm. In conclusion, maturation positively affects linear sprinting and linear RSA performance, whereas specific (multidirectional) RSA seems to be related to other factors.